Multifunctional Metal-Organic Frameworks for Photocatalysis - Wang, Sibo; Wang, Xinchen (Small (Weinheim an der Bergstrasse, Germany), 2015)
Metal–organic frameworks (MOFs) have attracted significant research attention in diverse areas due to their unique physical and chemical characteristics that allow their innovative application in various research fields. Recently, the application of MOFs in heterogeneous photocatalysis for water splitting, CO2 reduction, and organic transformation have emerged, aiming at providing alternative solutions to address the world‐wide energy and environmental problems by taking advantage of the unique porous structure together with ample physicochemical properties of the metal centers and organic ligands in MOFs. In this review, the latest progress in MOF‐involved solar‐to‐chemical energy conversion reactions are summarized according to their different roles in the photoredox chemical systems, e.g., photocatalysts, co‐catalysts, and hosts. The achieved progress and existing problems are evaluated and proposed, and the opportunities and challenges of MOFs and their related materials for their advanced development in photocatalysis are discussed and anticipated. Metal–organic frameworks (MOFs) have shown great promise in heterogeneous catalysis for energy and environment applications. This review summarizes the latest development of MOFs as multifunctional materials for photoredox catalysis to operate solar‐to‐chemical‐energy transformations according to their different roles in the photochemical systems, i.e., photocatalysts, co‐catalysts, and hosts.